A Survey of Technology Readiness Level Users. Issue 1 (13th September 2016) - Tomaschek, Katharina; Olechowski, Alison; Eppinger, Steven; Joglekar, Nitin
Abstract: The Technology Readiness Level (TRL) method, used to assess the maturity of a technology, has been applied in different industries for over 40 years. TRLs assist engineers in managing risks, communicating development progress and specifying deliverables. As TRLs have been adopted in more industries, the original scope of TRL application has expanded and challenges in use have emerged. Little is known about the TRL user community and its opinions of the method, or of the method's practical challenges. A global industry survey, conducted with professional TRL users, investigated the relative importance of 15 previously identified challenges of TRL use. We find that the top four most critical TRL challenges as identified by our respondents are system‐related; they include the topics of integration, interfaces, system modifications, and overall system maturity. The results reveal a need for an extension of the TRL method from a component‐readiness‐context to a system‐readiness‐context.